Effect of binocular visual function training on the reconstruction of binocular visual function in postoperative patients with intermittent exotropia - Wen-Shan Jiang (Guoji Yanke Zazhi, 2018)
AIM: To explore the effect of binocular visual function training on the reconstruction of binocular visual function and maintaining the stable eye position in postoperative patients with intermittent exotropia. METHODS: A total of 142 patients with intermittent exotropia underwent strabismus surgery in our hospital from January 2010 to December 2015 were enrolled. These patients were divided into two groups according to whether had binocular visual function training after surgery. The treatment group was used the DV-100 system to train the three-level visual function after surgery. For the control group, no intervention was performed after the operation. Respectively analysis the differences of binocular visual function and eye position in the two groups of patients before and 1mo after surgery, 3mo after surgery, 6mo after surgery, and 1a after surgery. RESULTS: The rate of the positive eye position in the treatment group was higher than the control group in the 6mo and 1a after surgery, and statistically significant difference was found(P<0.05). In 1, 3, 6mo and 1a after surgery, there were statistically significant differences in binocular visual function between the two groups. The recovery of binocular visual function in the treatment group was significantly better than that in the control group. CONCLUSION: The binocular visual function may have a certain degree of recovery in the patients with intermittent exotropia after surgery to obtain positive eye position. Through the postoperative visual perception learning and binocular visual function training, the binocular visual function can be better and faster recovered and reconstructed so as to obtain stereoscopic vision. It can better stabilize the eye position and help to reduce the rate of the patient's eye position fallback after surgery.